(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2009)
This was a prospective comparative study between conventional and automated culture system for isolation of Mycobacterium tuberculosis. Sputum samples from 138 clinically diagnosed cases of pulmonary tuberculosis from Institute of Disease of the Chest & Hospital, Dhaka, Bangabandhu Sheikh Mujib Medical University, Dhaka & Combined Military Hospital, Dhaka were collected and culture was carried out in both conventional Lowenstein- Jensen (L-J) media & MB-BacT automated culture system to compare the recovery rate, mean detection time and contamination rate. The study was carried out at the Armed Forces Institute of Pathology, Dhaka Cantonment, between March 2000 and January 2001. Out of the 138 specimens, 87 were culture positive. Among these, 83 cases (95.40%) were detected by MB/BacT and 74 cases (85.06%) by L-J media. The difference was statistically significant (p < 0.05). Statistically significant difference (p < 0.05) was also observed for smear negative culture positive cases (41 & 32 respectively). Of the total 87 culture positive cases, 70 were detected by both the systems but among the rest, MB/BacT alone detected 13 cases & L-J media alone detected only 04 cases. The difference was statistically significant (p < 0.05). The mean detection times for smear positive culture positive cases (41 sample) on an average were 9.24 days by MB/Bac T system and 20.6 days by L-J media. While for smear negative culture positive cases (45 sample), the figures were 18.50 and 27.50 days respectively. All the differences were statistically significant (p < 0.05). MB/BacT system showed less contamination rate, 05 cases (3.62%) in contrast to the 07 cases (5.07%) for L-J method. This difference also reached statistically significant (p < 0.05). The MB/BacT system thus found to be superior method of choice especially for handling large number of specimens. Key Words: Automated culture system, Mycobacterium tuberculosis. doi: 10.3329/jafmc.v5i1.2844 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.14-17